Comparative Phytochemical Screening, Antioxidant and Anti-Inflammatory Evaluation of In vitro Developed and Naturally Grown Geodorum densiflorum (Lam.) Schltr. of Bangladesh (Plant Tissue Culture and Biotechnology, 2026)
Geodorum densiflorum (Lam.) Schltr. is an endangered terrestrial orchid of Bangladesh having significant ornamental and medicinal value. To facilitate its conservation and validate its pharmaceutical potential, an efficient in vitro propagation protocol was established, followed by a comparative evaluation of phytochemical and biological activities between in vitro raised and naturally grown plant parts. Asymbiotic seed germination was evaluated on four basal media viz. MS, PM, KC and MVW supplemented with or without PGRs (0.5 mg/l BAP + 0.5 mg/l NAA). The highest seed germination (66.67%) and earliest protocorm development (14.00 ± 0.30 weeks) were recorded on MS medium supplemented with 0.5 mg/l BAP and 0.5 mg/l NAA. Qualitative phytochemical screening of methanolic extracts revealed alkaloids, flavonoids, tannins and other secondary metabolites in both wild and in vitro plantlets. In vitro plantlets showed particularly high levels of phlobatannins and phenolics compared to field grown plant parts. In biological assays, in vitro developed plantlets exhibited significant antioxidant potential (61.58% DPPH scavenging activity at 250 µg/ml), surpassing the activity observed in natural leaf, root and pseudobulb extracts. However, the anti-inflammatory activity (albumin denaturation inhibition) was higher in natural pseudobulb (81.81%) compared to in vitro plantlets (54.55%). This study establishes a reproducible protocol for mass propagation and confirms that in vitro derived G. densiflorum retains therapeutic properties, offering a sustainable alternative to wild harvesting.Plant Tissue Cult. & Biotech. 35(2): 407-416, 2025 (December)